PERFORMATIVITAS HUDSON PRANANJAYA DALAM PERTUNJUKAN MUSIK - Pratama, Zamrud Whidas; Vivian, Yofi Irvan (Fakultas Ilmu Budaya, Universitas Mulawarman, 2020)
Hudson Prananjaya is a singer who has a unique performance that is able to sing in the colors of the voice of men and women like a couple who is a duet. One of the songs he once brought back was the Gethuk song. The purpose of this study is to examine how the performance of a Hudson Prananjaya in exploring the gethuk song so that it has the characteristics of other singers. The theory used in this research is the theory of performativity, Habitus. This study aims to describe how Hudson's performativity in gethuk songs. Data collection is done by (1) literature study, (2) observation, (3) interview, (3) documentation. The stages in analyzing data with (1) data reduction, (2) data presentation, and (3) histography writing (4) conclusion. Clarification of the data was again carried out both to the subject of the study and to other informants. Hudson gained cultural insight in singing because he was accustomed to experimenting in singing. One of the songs that was brought back was Gethuk song. The visual aspect is shown by the concept of two face shows nuances of Javanese customs both makeup and clothes. The results of the transcription and analysis of musical aspects in the introduction section are marked with X sung using the basic tone of Fis Major by taking the first verse of the song yen ing tawang ono latitude. The introduction is sung in a free vocal style without a tempo called the recitative vocal style. Modulation to the Bes Major scale occurs when getting to the Gethuk song starts from the song intro until the song is finished. The gethuk song that Hudson reproduces back to part B (b1 '), (b2'). In the repetition section there is a dialogue technique in singing called unpicth vocal technique.